The Essence of Innovative Development of the Contemporary Education System in Modern Society - Kolesov, Vladimir Ivanovich (International Journal of Psychosocial Rehabilitation, 2020)
The article presents the key ideas of the methodological system for measuring the innovative development of education from the point of view of a holistic approach to the human development in modern Russia. Only through education, self-education a person reaches the very top of the "Acme", that is, the perfection of himself.